(untitled) (Journal of Computational Mathematics, 2022)
The operators radiative transfer equation constructed by Chandrasekhar has been extended to the non-stationary case by Bellman and Wang. The local existence of solution of such non-stationary equation is established based on the construction of scattering matrices from a co-propagation group with unbounded generator. In case the system is dissipative, the local existence will extend to the global existence.